2022
DOI: 10.56892/bimajst.v6i02.358
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Platform Approach Using Hybrid Deep Learning Models for Automatic Detection of Hate Speech on Social Media

Abstract: Hate speech on online social networks is a general problem across social media platforms that has the potential of causing physical harm to the society. The growing number of hateful comments on the Internet and the rate at which tweets and posts are published per second on social media make it a challenging task to manually identify and remove the hateful commentsfrom such posts. Although numerous publications have proposed machine learning approaches to detect hate speech and other antisocial online behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Work by [44] established the CNN's efficacy in text classification tasks, inspiring subsequent research in offensive language detection. Moreover, Recurrent Neural Networks (RNNs) and their advanced variant, Long Short-Term Memory networks (LSTMs), have gained prominence for their aptitude in handling sequential data, offering a deeper understanding of contextual information in sentences [45]. This attribute is crucial in deciphering offensive content embedded in conversational threads or sentences reliant on context for interpretation [46].…”
Section: E Deep Learning In Offensive Language Detectionmentioning
confidence: 99%
“…Work by [44] established the CNN's efficacy in text classification tasks, inspiring subsequent research in offensive language detection. Moreover, Recurrent Neural Networks (RNNs) and their advanced variant, Long Short-Term Memory networks (LSTMs), have gained prominence for their aptitude in handling sequential data, offering a deeper understanding of contextual information in sentences [45]. This attribute is crucial in deciphering offensive content embedded in conversational threads or sentences reliant on context for interpretation [46].…”
Section: E Deep Learning In Offensive Language Detectionmentioning
confidence: 99%
“…Simon et al [19] showed a systematic review of machine learning trends in the automatic detection of hate speech on social media platforms. A total of 31,714 articles from 2015 to 2020 were examined; 41 papers were included based on inclusion criteria, while 31,673 papers were excluded according to exclusion criteria.…”
Section: Related Workmentioning
confidence: 99%